2019
DOI: 10.1136/bmjresp-2019-000431
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarkers and outcomes in patients with moderate COPD: a substudy of the randomised SUMMIT trial

Abstract: RationaleSystemic levels of C reactive protein (CRP), surfactant protein D (SPD), fibrinogen, soluble receptor of activated glycogen end-product (sRAGE) and club cell protein 16 (CC-16) have been associated with chronic obstructive pulmonary disease (COPD) outcomes. However, they require validation in different cohorts.ObjectivesRelate systemic levels of those proteins to forced expiratory volume in 1 s (FEV1) decline, exacerbations, hospitalisations and mortality in COPD patients (FEV1 of ≥50 and ≤70% predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 45 publications
1
29
1
3
Order By: Relevance
“…28 However, analyzing the SUMMIT data, the levels of systemic inflammatory biomarkers did not relate to the frequency of flare-ups. 29 Interestingly we found that the highest FVC quintile was associated with an increased exacerbation risk. This, together with the gradually increased risk for exacerbation with FEV 1 decline suggest that more severe emphysema may be related to higher number of exacerbations.…”
Section: Discussionmentioning
confidence: 59%
“…28 However, analyzing the SUMMIT data, the levels of systemic inflammatory biomarkers did not relate to the frequency of flare-ups. 29 Interestingly we found that the highest FVC quintile was associated with an increased exacerbation risk. This, together with the gradually increased risk for exacerbation with FEV 1 decline suggest that more severe emphysema may be related to higher number of exacerbations.…”
Section: Discussionmentioning
confidence: 59%
“…15,16 However, the findings on systemic inflammation biomarkers and clinical characteristics of COPD are contradictory. [15][16][17][18][19][20][21] In this way, it is essential to investigate the cell line responsible for synthesizing cytokines that orchestrate inflammation in stable COPD. 22 In addition, exploring correlations not previously investigated between the intracellular inflammatory profile and clinical characteristics and functional status, may contribute to the management of this heterogeneous group of patients, with more promising results and better outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the observed sputum color remains highly sensitive and specific for a high bacterial load during such episodes. The SUMMIT trial failed to show the benefit of using CRP, SPD, s RAGE, CC-16, and fibrinogen to predict forced expiratory volume in 1 st second (FEV 1 ) decline, hospitalization, or exacerbation [4]. Continued cautious and realistic interpretation of the role of biomarkers in the management of identified clinical traits is needed.…”
mentioning
confidence: 99%